Comparative Metagenomic Profiling of Seed-Borne Microbiomes in a Landrace and a Hybrid Maize Variety - Sarah Henaut-Jacobs; Beatriz Elisa Barcelos Cyríaco; Francisnei Pedrosa-Silva; Fabio Lopes Olivares; Thiago Motta Venancio (Seeds)
The plant seed-borne microbiome comprises microorganisms vertically inherited from the mother plant. This microbiome is often linked to early-life protection and seedling growth promotion. Herein, we compare the seed-borne bacteriomes of a commercial hybrid (Santa Helena) and a landrace maize variety (Sol da Manhã). The landrace variety displays a more diverse seed-borne microbiome, featuring a variety of taxa across samples with an average Shannon’s diversity index of 1.12 compared to 0.45 in the hybrid variety. The landrace variety also showed a greater alpha diversity of 165.8, in contrast to 144.1 in the hybrid. Although both microbiomes lack a functional nitrogen fixation apparatus, we found a remarkably distinct presence of genes associated with phytohormone production and phosphate solubilization, particularly in the landrace variety. In addition, we recovered 18 metagenome-assembled genomes (MAGs), including four from potentially novel species. Collectively, our results allow for a better understanding of the contrasting diversity between maize varieties. The higher potential for phytohormone production in landraces, the absence of nif genes in both varieties, and the identification of core microbiome taxa offer valuable insights into how microbial communities impact plant health and development. This knowledge could pave the way for more sustainable and innovative agricultural practices in crop management.